A projection-based particle method with optimized particle shifting for multiphase flows with large density ratios and discontinuous density fields. (30th January 2019) - Khayyer, Abbas; Gotoh, Hitoshi; Shimizu, Yuma
Highlights: A multiphase projection-based particle method for flows of large density ratios and discontinuous density fields. A computational algorithm on the basis of optimized particle shifting is incorporated for interface stabilization. Validations and comparisons are conducted through several multiphase benchmark tests. An extended version of an iterative shifting scheme is implemented and tested. The present study portrays the robustness of particle shifting concept for multiphase particle-based simulations. Abstract: A novel projection-based particle method is presented for simulation of multiphase flows characterized by large density ratios and discontinuous density fields at the phase interface. The method considers a multi-fluid continuous system and comprises of a specific computational algorithm utilizing the recently developed Optimized Particle Shifting (OPS[1] ) scheme to maintain the regularity of particles at the phase interface and free-surface. The method is founded on an improved version of Moving Particle Semi-implicit (MPS[2] ) as a projection-based particle method. A set of previously developed improved schemes are also adopted and hence the proposed method is referred to as improved MPS + OPS. Validations are made both qualitatively and quantitatively in terms of accuracy, energy conservation properties as well as convergence properties by consideration of several benchmark tests.